European Airline Mergers, Alliance Consolidation, and Consumer Welfare - Jan K. Brueckner; Eric Pels (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper explores the effects of a European airline merger followed by a consolidation of two competing international alliances. The exercise has been inspired by the Air France-KLM merger, which is expected to spur consolidation of the Northwest-KLM and SkyTeam alliances into a single mega-alliance. The results of the analysis show that, although the airlines benefit through higher profits, the merger and alliance consolidation harm consumers while reducing overall social surplus. The reason for this negative outcome is that, as modeled, all the effects of the merger and alliance consolidation are anticompetitive.
Keywords: 330; european airline merger; airlines; airline alliance; transportation